Influence of the staphylococcinlike peptide Pep 5 on membrane potential of bacterial cells and cytoplasmic membrane vesicles. - Sahl, H G (1985)
The staphylococcinlike peptide Pep 5 rapidly abolished the membrane potential of bacterial cells; active transport of amino acids by cytoplasmic membrane vesicles was inhibited and preaccumulated amino acids were released upon the addition of Pep 5. Artificial asolectin vesicles were not impaired by the peptide. It is concluded that the cytoplasmic membrane is the primary target of Pep 5.